2015
DOI: 10.1038/emi.2015.42
|View full text |Cite
|
Sign up to set email alerts
|

NovelkatGmutations causing isoniazid resistance in clinicalM. tuberculosisisolates

Abstract: We report the discovery and confirmation of 23 novel mutations with previously undocumented role in isoniazid (INH) drug resistance, in catalase-peroxidase (katG) gene of Mycobacterium tuberculosis (Mtb) isolates. With these mutations, a synonymous mutation in fabG1g609a, and two canonical mutations, we were able to explain 98% of the phenotypic resistance observed in 366 clinical Mtb isolates collected from four high tuberculosis (TB)-burden countries: India, Moldova, Philippines, and South Africa. We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 60 publications
2
77
0
1
Order By: Relevance
“…As well as providing an accurate diagnosis for MDR-TB, LPAs also provide information about the level of INH resistance, depending on the mutation detected. 16 Katiyar et al compared high doses of INH (16–18 mg/kg), a normal dose of INH and placebo in a trial of 123 MDR-TB subjects. They found that high doses of INH led to rapid culture negativity of sputum and increased the likelihood of sputum being negative by month 6 of treatment compared with the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…As well as providing an accurate diagnosis for MDR-TB, LPAs also provide information about the level of INH resistance, depending on the mutation detected. 16 Katiyar et al compared high doses of INH (16–18 mg/kg), a normal dose of INH and placebo in a trial of 123 MDR-TB subjects. They found that high doses of INH led to rapid culture negativity of sputum and increased the likelihood of sputum being negative by month 6 of treatment compared with the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although the mutations that we identified provide a larger picture of the genetic basis of phenotypic antituberculosis drug resistance, they do not represent a complete genetic profile of the DR-TB specimens evaluated in this study. The inclusion of other gene regions, such as novel katG and fabG1 mutations recently associated with INH resistance (32), may further increase the sensitivity of rapid molecular diagnostic assays for DR-TB detection. Additional sequencing studies investigating other genes and gene regions, such as tlyA and gidB mutations and their association with injectable resistance (12), will be necessary to identify the genetic basis of drug resistance for the 4 to 16% of genetically wild-type, drugresistant specimens in this study.…”
Section: Rifmentioning
confidence: 99%
“…The current model of exclusively using molecular diagnostics to target INH resistance mutations inside of “hotspots” may ultimately select for clinical strains that have non-canonical INH resistance mutations by depleting those with common ones from the host population. This scenario was already hypothesized by Torres and colleagues, who found >20 clinical katG mutations outside codon S315 by WGS of and used site-directed mutagenesis to show that several could independently confer INH resistance to Mycobacterium smegmatis (43). There is evidence to suggest that the rise of non-canonical INH resistance mutations is already happening in India, where there is a high burden of drug-resistant TB (65).…”
Section: Discussionmentioning
confidence: 67%
“…Likewise, N138S, W300R, S315G, S315N, W328R were also expected to increase the INH MIC since mutations at all of those residues are associated with decreased INH-NADH adduct (active drug) formation in biochemical studies of KatG enzyme (40). Notably, the W161Q, W161R, E402stop, L415P, and A480del mutations were not reported in the literature and A110V has only been reported in the presence of other confounding mutations (43, 64).…”
Section: Discussionmentioning
confidence: 99%